No Robust Association between Static Markers of Testosterone and Facets of Socio-Economic Decision Making - Kaltwasser, Laura; Mikac, Una; Buško, Vesna; Hildebrandt, Andrea (Frontiers in Behavioral Neuroscience, 2017)
Digit ratio (2D:4D) and facial width-to-height ratio (WHR) are supposedly static indicators of testosterone exposition during prenatal and pubertal lifetime, respectively. Both measures have been linked to aggressive and assertive behavior in laboratory economic games, as well as in real world scenarios. Most of the research – often limited to male subjects – considers the associations between these behaviors, traits, and hormonal markers separately for 2D:4D and WHR. Reported associations are weak and volatile. In the present study we had independent raters assess 2D:4D and WHR in a sample of N=175 participants who played the ultimatum game (UG). Respondent behavior in UG captures the tendency to reject unfair offers (negative reciprocity). If unfair UG offers are seen as provocations, then individuals with stronger testosterone exposition may be more prone to reject such offers. Economists argue that negative reciprocity reflects altruistic punishment, since the rejecting individual is sacrificing own resources. However, recent studies suggest that self-interest, in terms of status defense plays a substantial role in decisions to reject unfair offers. We also assessed social preferences by social value orientation and assertiveness via self-report. By applying structural equation modelling we estimated the latent level association of 2D:4D and WHR with negative reciprocity, assertiveness and prosociality in both sexes. Results revealed no robust association between any of the trait measures and hormonal markers. The measures of 2D:4D and WHR were not related with each other. Multigroup models based on sex suggested invariance of factor loadings allowing to compare hormone-behavior relationships of females and males. Only when collapsing across sex greater WHR was weakly associated with assertiveness, suggesting that individuals with wider faces tend to express greater status defense. Only the right hand 2D:4D was weakly associated with prosocial behavior, indicating that individuals with lower prenatal testosterone exposure are more cooperative. Rejection behavior in UG was not related with 2D:4D nor WHR in any of the models. There were also no curvilinear associations between 2D:4D and prosociality as theorized in the literature. Our results suggest that previous studies over-estimated the role of static markers of testosterone in accounting for aggression and competition behavior.